The Influence of Snowball Throwing Learning Model with Contextual Approach on Critical Mathematical Thinking Skills and Students' Self Confidence Grade VIII MTs Ma'Arif NU 1 Kedungbanteng - Marsilia, Devi; Kumala, Fitria Zana (UM Purwokerto Press, 2025)
This research is motivated by the critical thinking ability of mathematical and self-confidence of grade VIII students of MTs Ma’arif NU 1 Kedungbanteng which are still relatively low. The learning process that encourages the development of students' cognitive and affective abilities is influenced by the learning model used in the learning process itself. The purpose of this study was to analyze whether the snowball throwing learning model with a contextual approach has an effect on students' critical thinking ability of mathematical and self-confidence. This research is a field research using quantitative methods and an experimental approach. The population of this study was all 8th grade students totaling 161, with random sampling obtained 8th grade B as the control class and 8th grade D as the experimental class. The data analysis technique used the N-Gain test, normality test, homogeneity test, and t-test. Based on the results of the study, there is an influence of the snowball throwing learning model with a contextual approach on students' critical mathematical thinking skills and self-confidence. This is evidenced by the significance of the independent sample t-test on the average N-Gain value of 0.001 <0.05. The average N-Gain of the experimental class is 0.611 which is included in the fairly effective category and higher than the average N-Gain of the control class of 0.375 which is included in the ineffective category.